2009
DOI: 10.1107/s1600536809026944
|View full text |Cite
|
Sign up to set email alerts
|

Bis(creatininium) tetrachloridocadmate(II)

Abstract: In the title compound, (C4H8N3O)2[CdCl4], the asymmetric unit comprises two creatininium cations and one tetra­chloridocadmate anion. Cd⋯O secondary bonding links one of the two imidazole rings and the anion into ion pairs. The free and bound cations form layers between which the [CdCl4]2− anions are sandwiched. The CdII atom adopts a distorted trigonal-bipyramidal geometry in which the Cd⋯O bond is axial. Inter­molecular N—H⋯Cl hydrogen bonds form a two-dimensional network parallel to (001) which ensures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A search of the Cambridge Structural Database (Version 5.38, update May 2017; Groom et al, 2016) revealed that the geometric parameters of the title compound are similar to those found in bis(creatininium) tetrachloridocadmate(II) (Boufas et al, 2009). The imidazol group conformation of the title compound is in contrast to the bent gauche conformation found in the structure of l-HisH + ÁCl À ÁH 2 O (Donohue et al, 1956(Donohue et al, , 1964, but similar to the trans conformation observed in dl-HisH + ÁCl À Á2H 2 O (Steiner, 1996)…”
Section: Database Surveymentioning
confidence: 92%
See 1 more Smart Citation
“…A search of the Cambridge Structural Database (Version 5.38, update May 2017; Groom et al, 2016) revealed that the geometric parameters of the title compound are similar to those found in bis(creatininium) tetrachloridocadmate(II) (Boufas et al, 2009). The imidazol group conformation of the title compound is in contrast to the bent gauche conformation found in the structure of l-HisH + ÁCl À ÁH 2 O (Donohue et al, 1956(Donohue et al, , 1964, but similar to the trans conformation observed in dl-HisH + ÁCl À Á2H 2 O (Steiner, 1996)…”
Section: Database Surveymentioning
confidence: 92%
“…In this work, we report the synthesis and structure of the title cadmium complex with l-histidine, (I). Cadmium is structurally interesting as it exhibits a number of coordination numbers and geometries such as those in [CdCl 4 ] (Boufas et al, 2009), [Cd 3 Cl 11 ] (Kurawa et al, 2008), [CdCl 6 ] n (Jarboui et al, 2011) and [CdCl 4 ] n (Loseva et al, 2010).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The anionic metal-halide species has been observed to range in dimensionality from zero-dimensional (0D) clusters to three-dimensional frameworks. In fact, along with the rich structural diversity displayed by these systems, the cadmium halide compounds in combination with organic cations have been highlighted, due to the fact that they show a high variety of coordination numbers and geometries [14][15][16][17]. In a previous work, we have described (N,N-dimethylbenzylammonium)trichlorocadmate as a hybrid material containing the [CdCl 3 ] -anion [16], which is known to crystallize in the monoclinic system with the space group Cc .…”
Section: Introductionmentioning
confidence: 97%